2018
DOI: 10.25077/jka.v7.i1.p65-73.2018
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Peran Manajer dengan Pelaksanaan Pencegahan dan Pengendalian Infeksi Rumah Sakit di Ruang Rawat Inap Bedah RSUP Dr.M.Djamil Padang Tahun 2016

Abstract: Infeksi Rumah Sakit saat ini merupakan salah satu penyebab meningkatnya angka kesakitan (morbidity) dan angka kematian (mortality) di rumah sakit. Kepala ruangan sebagai manajer harus terus membina stafnya agar program pengendalian infeksi berjalan sesuai kesepakatan. Tujuan penelitian ini adalah mengetahui hubungan peran manajer dengan pelaksanaan pencegahan dan pengendalian infeksi rumah sakit di ruang rawat inap bedah RSUP Dr.M.Djamil Padang tahun 2016. Penelitian ini bersifat deskriptif menggunakan metode … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In carrying out their role as front-line manager, room's leader in hospital played a role as the manager for the IPC program. Several studies have shown that the implementation of role and function of room's leader greatly affected infection prevention and control, especially in the nurse's compliance of implementing IPC efforts (17)(18)(19)(20). The absence or inferior role of the room's leader could lead to poor performance in the implementation of the IPC program.…”
Section: Role and Function Of Room's Leadermentioning
confidence: 99%
“…In carrying out their role as front-line manager, room's leader in hospital played a role as the manager for the IPC program. Several studies have shown that the implementation of role and function of room's leader greatly affected infection prevention and control, especially in the nurse's compliance of implementing IPC efforts (17)(18)(19)(20). The absence or inferior role of the room's leader could lead to poor performance in the implementation of the IPC program.…”
Section: Role and Function Of Room's Leadermentioning
confidence: 99%